Urgensi Integrasi Nasional sebagai Salah Satu Parameter Persatuan dan Kesatuan Bangsa - Taun, Taun; Ardiansyah, Acep Kiki; Azra, Alia Aida; Hikmah, Rizkatul; Ma’mun, Shaummadini Putri; Khodijah, Siti (Indo-MathEdu Intellectuals Journal, 2024)
This article outlines that national integration can be used as one of the main parameters in assessing the integrity and cohesiveness of a country. This research uses a qualitative approach through the literature review method to explain that national integration not only involves political and economic aspects, but also social, cultural and national identity. This research tries to explore and analyze the problems to be answered through the results of the analysis of various relevant references such as research articles, reference books, and other relevant sources. Data collection is carried out by searching for various articles of the last 10 years (2014 to 2024) published on google scholar. The data analysis process is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that without effective integration, various challenges such as disintegration, social conflict and political instability can threaten national unity. The author concludes that national integration must be strengthened through inclusive and participatory policies to realize sustainable unity